Passing the Traditional Lesson with the Help of Open Moodle Platforms - Ismatovna, Asadova Yulduz. (Research Parks Publishing LLC, 2021)
Moodle is one of the modern open platforms that can be used for distance learning, which is a package of programs that can be used to create e-courses. This is an education management system-LMS, which ensures good cooperation between teachers and students. The article deals with the issues of improving the quality of traditional learning using the electronic platform Moodle to effective independent e-learning. The methods of using various Moodle tools to provide interactive and stimulating learning while providing a location-based education by the teacher based on the information on the topics given on the basis of the program are also indicated; how with these tools students will develop their independent cognitive skills in various higher education institutions.